Development of an item pool for a questionnaire on the psychosocial consequences of hypertension labelling - János Valery Gyuricza; Ana Flávia Pires Lucas d'Oliveira; Lucas Bastos Marcondes Machado; John Brodersen (SpringerOpen, 2019)
Abstract Background Hypertension is the most prevalent risk factor for cardiovascular disease globally. Roughly one-third of the adult population has hypertension. However, most people diagnosed with hypertension do not benefit from blood pressure control with pharmacologic interventions: they are overdiagnosed and overtreated and might experience negative psychosocial consequences of being labelled. These consequences are relevant outcomes that need to be assessed and validly measured to identify all benefits and harms related to interventions designed to prevent cardiovascular disease. Objectives To develop a pool of items with high content validity for a draft version of a condition-specific questionnaire to measure the psychosocial consequences of being labelled with mild hypertension. Methods We selected relevant items from existing Consequences of Screening (COS) questionnaires. These items belonged to two groups: COS core items and potential condition-specific items. All items were originally in Danish and were translated into Brazilian Portuguese using the dual-panel method. Individual and group interviews were conducted with people with mild hypertension and low risk for cardiovascular disease, and were designed to test the translated items for face and content validity and were also used to generate new relevant items. Structured individual interviews were conducted to categorise all the items into domains. Results The Brazilian Portuguese dual-panel translation of both groups of items was found to be relevant for adults diagnosed with hypertension. We generated 52 new items to achieve high content validity. The result was a set of 132 items divided into 22 domains in 2 parts. Part I was directed at the general population, whereas part II was directed only at people diagnosed with hypertension and it consisted of 38 items in 8 domains. Twelve items remained as single items. High content validity was achieved with the pool of 132 items divided into 22 domains in 2 parts. Discussion High content validity was achieved for a condition-specific questionnaire measuring the psychosocial consequences of being labelled with mild hypertension. This instrument encompassed 132 items divided into 22 domains in 2 parts. Thereby, a draft of the Consequneces of Hypertension questionnaire (COH) was developed. The psychometric properties of this questionnaire will be discussed in a diferent paper.